The winding road to discovering iPS cells : the life of Yamanaka Shinya - Yamanaka, Shinya; Midori, Shin'ya, 1976-; Atkinson, Tony, 1956- (Tokyo, Japan : Japan Publishing Industry Foundation for Culture (JPIC), 2021)
'The revolutionary discovery of induced pluripotent stem cells, or iPS cells, completely changed the world, particularly in the field of medical science. This groundbreaking achievement was made by Dr. Yamanaka Shinya of Kyoto University and won him the Nobel Prize for Physiology or Medicine in 2012. The road that led him to this accomplishment, however, was not an easy one; during his early days as a training orthopedic surgeon, Yamanaka was not skilled and was called'a hindrance' by his supervisor. He eventually changed course to become a researcher in the field of medical science and undertook postdoctoral studies in the United States, but he experienced a mild case of depression upon returning to Japan. Even when Yamanaka presented the results of his discovery of iPS cells, he could not immediately bask in the glory of his success, since many of his peers simply could not believe his achievement. In this volume, the Nobel Prize laureate talks openly about his life from his childhood days to his current daily life and discusses his views on the future of regenerative medicine. How were iPS cells developed and what can they do? Translated from a runaway bestseller in Japan and replete with a new preface for the English edition, this biography shows what science can do for mankind, and the possibilities that life holds.' --back cover.
First published in Japan in 2012 by Kodansha Ltd., Tokyo.
Includes bibliographic references (pages 146-147) and index.
Keywords: Yamanaka, Shinya; Biologists -- Japan -- Biography; Embryonic stem cells; Embryonic stem cells -- Research; Stem cells -- Therapeutic use